Challenges and Opportunities Facing Mataram English Teachers in Academic Publication - Dewi, Mahdalena; Yusra, Kamaludin; Lestari, Yuni Budi; Sujana, I Made (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study is aimed to identified challenges and opportunities facing Mataram English teachers in academic publication. The data of lecturer were collected by using questionnaire and interviews 25 junior high school English teachers in MGMP (Musyawarah Guru Mata Pelajaran) Bahasa Inggris Kota Mataram. The data were descriptively analyst by identifying, classifying, describing, explaining, the challenges and opportunities. The study found that time, academic writing skill, motivation, confidence, and supporting facilities an responsible to lack of academic publication amount English teachers. Nonetheless, opportunities is result from teachers in developing self in personal skill, writing skill, and skill in accessing academic resources for people wring in academic publication.